2022
DOI: 10.1167/jov.22.13.6
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial attention in crowding and feature binding

Abstract: Crowding refers to the failure to identify a peripheral object due to nearby objects (flankers). A hallmark of crowding is inner–outer asymmetry; that is, the outer flanker (more peripheral) produces stronger interference than the inner one. Here, by manipulating attention, we tested the predictions of two competing accounts: the attentional account, which predicts a positive attentional effect on the inner–outer asymmetry (i.e., attention to the outer flanker will increase asymmetry) and the receptive field s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…An alternative explanation for the differences in crowding magnitudes between paradigms could be a difference in their spatial attentional demand. Previous research has indicated that attentional cues can influence crowding ( Grubb, 2013 ; Kewan-Khalayly and Yashar, 2022 ; Kewan-Khalayly et al, 2022 ). It is arguably easier and likely more effective to attend to the two possible target locations of the 2AFC paradigms compared to the multiple locations in the other paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the differences in crowding magnitudes between paradigms could be a difference in their spatial attentional demand. Previous research has indicated that attentional cues can influence crowding ( Grubb, 2013 ; Kewan-Khalayly and Yashar, 2022 ; Kewan-Khalayly et al, 2022 ). It is arguably easier and likely more effective to attend to the two possible target locations of the 2AFC paradigms compared to the multiple locations in the other paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Though our star]ng point was different, our experimental manipula]ons resemble those in complementary research on the role of eccentricity and crowding in vision (e.g., [66][67][68][69][70][71][72][73][74] ) and visual working memory (e.g., [75][76][77] ). This literature has typically focused on other ques]ons, such as how visual resolu]on changes when moving from central to peripheral vision.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have been seeking effective ways to relieve crowding. Several studies have demonstrated that cueing of a crowded target location reduces the crowding effects ( Anton-Erxleben & Carrasco, 2013 ; Kewan-Khalayly, Migó, & Yashar, 2022 ; Kewan-Khalayly & Yashar, 2022 ; Talgar, Pelli, & Carrasco, 2004 ; Yeshurun & Carrasco, 1999 ), and modulating attentional allocation could affect inner–outer asymmetry ( Chakravarthi, Rubruck, Kipling, & Clarke, 2021 ; Kewan-Khalayly & Yashar, 2022 ; Kewan & Yashar, 2021 ; Petrov & Meleshkevich, 2011b ). However, the role of attentional modulation has still been controversial, as some studies have reported that it has little or even no effect on crowding ( Huckauf & Heller, 2002 ; Nazir, 1992 ; Scolari, Kohnen, Barton, & Awh, 2007 ; Wilkinson, Wilson, & Ellemberg, 1997 ).…”
Section: Introductionmentioning
confidence: 99%